Feeding in domestic vertebrates [ from structure to behaviour - Bels, Vincent (CABI, 2006)
The aim of this volume is to provide advanced students and researchers with a review of current knowledge of feeding in domestic mammals and birds. The first few chapters cover feeding structures and mechanisms in birds and mammals. The rest of the bookthen presents chapters on feeding behavior in particular species.